Comparison of Complete Genome Sequences of Usutu Virus Strains Detected in Spain, Central Europe, and Africa - Bakonyi, Tamás (Mary Ann Liebert, Inc., 2014)
The complete genomic sequence of Usutu virus (USUV, genus Flavivirus, family Flaviviridae) strain MB119/06, detected in a pool of Culex pipiens mosquitoes in northeastern Spain (Viladecans, Catalonia) in 2006, was determined and analyzed. The phylogenetic relationship with all other available complete USUV genome sequences was established. The Spanish sequence investigated showed the closest relationship to the USUV prototype strain SA AR 1776 isolated in South Africa in 1959 (96.9% nucleotide and 98.8% amino acid identities). Conserved structural elements and enzyme motifs of the putative polyprotein precursor were identified. Unique amino acid substitutions were recognized; however, their potential roles as virulence markers could not be verified. Comparisons of the polyprotein precursor sequences of USUV strains detected in mosquitoes, birds, and humans could not confirm the predicted role of unique amino acid substitutions in relation to virulence in humans. Phylogenetic analysis of a partial coding section of the NS5 protein gene region indicated that USUV strains circulating in Europe form three different genetic clusters. Broad and targeted surveys for USUV in mosquitoes could reveal further details of the geographic distribution and genetic diversity of the virus in Europe and in Africa.